Background Diet Influences TMAO Concentrations Associated with Red Meat Intake without Influencing Apparent Hepatic TMAO-Related Activity in a Porcine Model - Rebekka Thøgersen; Martin Krøyer Rasmussen; Ulrik K. Sundekilde; Sophie A. Goethals; Thomas Van Hecke; Els Vossen; Stefaan De Smet; Hanne Christine Bertram (Metabolites, 2020)
Red meat has been associated with an increased cardiovascular disease (CVD) risk, possibly through gut microbial-derived trimethylamine-N-oxide (TMAO). However, previous reports are conflicting, and influences from the background diet may modulate the impact of meat consumption. This study investigated the effect of red and white meat intake combined with two different background diets on urinary TMAO concentration and its association with the colon microbiome in addition to apparent hepatic TMAO-related activity. For 4 weeks, 32 pigs were fed chicken or red and processed meat combined with a prudent or western background diet. 1H NMR-based metabolomics analysis was conducted on urine samples and hepatic Mrna expression of TMAO-related genes determined. Lower urinary TMAO concentrations were observed after intake of red and processed meat when consumed with a prudent compared to a western background diet. In addition, correlation analyses between urinary TMAO concentrations and relative abundance of colon bacterial groups suggested an association between TMAO and specific bacterial taxa. Diet did not affect the hepatic Mrna expression of genes related to TMAO formation. The results suggest that meat-induced TMAO formation is regulated by mechanisms other than alterations at the hepatic gene expression level, possibly involving modulations of the gut microbiota.